Comparison of the efficacy and safety of third-line treatments for metastatic colorectal cancer: a systematic review and network meta-analysis - Gao, Loulu; Tang, Lin; Hu, Zixuan; Peng, Jieqiong; Li, Xiaoqian; Liu, Bo (Frontiers in Oncology, 2023)
The objective of this study is to evaluate the efficacy and safety of different third-line treatment regimens for metastatic colorectal cancer (mCRC) through a comprehensive analysis and network meta-analysis (NMA). Additionally, the study aims to provide guidance on selecting appropriate third-line systemic treatment regimens for patients with mCRC.We conducted a search of the PubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials databases from January 1, 2005, to May 20, 2023, to include phase II/III randomized clinical trials (RCTs) of third-line treatments for mCRC. The primary outcome assessed in the NMA was median overall survival (mOS), and other outcomes included median progression-free survival (mPFS), disease control rate (DCR), and grade 3 or higher adverse events (≥3AEs).Results: Ultimately, nine phase II/III RCTs involving five treatment regimens were included in this study. Trifluridine/tipiracil (TAS-102) plus bevacizumab (hazard ratio [HR] 0.41, 95% credible interval [CrI] 0.32-0.52) was found to be the most effective treatment for mOS compared to best supportive care (BSC). TAS-102 plus bevacizumab also significantly improved mPFS compared to BSC (HR 0.20, 95% CrI 0.16-0.25). In terms of adverse events (AEs), TAS-102 (RR 0.52, 95% CrI 0.35-0.74) had a lower incidence of ≥3AEs compared to fruquintinib, but fruquintinib (RR 1.79, 95% CrI 1.10-3.11) showed better improvement in DCR than TAS-102. Subgroup analysis using the Bayesian surface under the cumulative ranking curve (SUCRA) ranked the regimens based on the OS benefit. The results indicated that TAS-102 plus bevacizumab ranked first across age, gender, Eastern Cooperative Oncology Group performance status (ECOG PS), and time from initial diagnosis of metastatic disease to randomization.Conclusions: TAS-102, fruquintinib, TAS-102 plus bevacizumab, the regorafenib standard dose regimen (regorafenib), and the regorafenib dose-escalation regimen (regorafenib 80+) all demonstrated improved OS and PFS compared to BSC in mCRC patients. However, TAS-102 plus bevacizumab may be the optimal choice for third-line treatment in mCRC patients.